High efficacy of the F-ATP synthase inhibitor TBAJ-5307 against nontuberculous mycobacteria in vitro and in vivo - Ragunathan, Priya (2024)
The F1FO-ATP synthase engine is essential for viability and growth of nontuberculous mycobacteria (NTM) by providing the biological energy ATP and keeping ATP homeostasis under hypoxic stress conditions. Here, we report the discovery of the diarylquinoline TBAJ-5307 as a broad spectrum anti-NTM inhibitor, targeting the FO domain of the engine and preventing rotation and proton translocation. TBAJ-5307 is active at low nanomolar concentrations against fast- and slow-growing NTM as well as clinical isolates by depleting intrabacterial ATP. As demonstrated for the fast grower Mycobacterium abscessus, the compound is potent in vitro and in vivo, without inducing toxicity. Combining TBAJ-5307 with anti-NTM antibiotics or the oral tebipenem–avibactam pair showed attractive potentiation. Furthermore, the TBAJ-5307–tebipenem– avibactam cocktail kills the pathogen, suggesting a novel oral combination for the treatment of NTM lung infections.